The use of prepared instructional music programs and artificial intelligence in the teaching process and their role in developing the ability of students in the Department of Art Education - محمود, م.م. تۆڵە ئومێد محمود (Sulaimani Journal for Humanities, 2025)
The aim of the research use several prepared educational programs and artificial intelligence in teaching music subjects (music taste - music theory - general solfege - main instrument) in the Art Education Department for the academic year (2025-2026). And to know the role of these music programs in music education and developing the capabilities of students in the Art Education Department. The descriptive approach was adopted in implementing the research according to the nature of its topic and objectives. The research community consisted of students of the Art Education Department (morning - evening). As for the study sample, it consisted of second-grade students (morning - evening) for the academic year (2024-2025). According to the procedures and steps taken in the third part, the researcher identified the music programs through discussions with music teachers in the Department of Art Education and the Department of Music. They were then directed to music experts. The researcher then asked the study sample several questions about their level of use of the prepared music programs and artificial intelligence through a closed questionnaire and presented them with the music programs. Finally, the research reached results. The programs that were identified as enjoyable and easy to learn covered all aspects of the lesson, including two artificial intelligence programs (Top Media ai-Suno) for the subject (music taste), four prepared music educational programs (Music tutor- Solfa- Music theory helper- Note rote) for the subject (music theory), four prepared music educational programs (Complete Rhythm Trainer- Solfege Practice- Sight Singing- NotesDe musique) for the subject (general solfege), and one artificial intelligence program (Yousician) for learning the piano for the subject (main instrument).
Keywords: Music Artificial Intelligence Program; music prepared; instructional programs; Direction of students